'Over-indebtedness' – or not? Household debt accumulation and risk exposure in nineteenth century Sweden. Issue 1 (2nd January 2022) - Lindgren, Håkan
ABSTRACT: In light of the ongoing extensive discussion concerning the increasing financial risk levels of the household sector in modern, credit-based societies, this study explores the level and structure of credit markets in nineteenth century Sweden. The growing international research focusing on informal credit markets outside formalised institutions has demonstrated that credit was abundantly and pervasively included in the lion's share of all inter-personal financial relationships in early modern Europe. In this particular study, based on probate inventories and the inverted mortality method, the changing structure of nineteenth century credit market is estimated for the living population. The household financial situation is studied as life-cycle indebtedness and as debt ratios in relation to income, wealth and financial assets and how these ratios evolved during the transformation from a predominately agrarian to a more commercialised, monetised and industrialised economy in Sweden during the nineteenth century. The source material for this article consists of more than 5800 household probate inventories from Southern and Central Sweden, including three rural and two urban areas. The geographical selection is based on a sample utilised in a wider research project. It permits comparisons of debt structures not only between rural and urban areas, but also among different regions within Sweden.